Delivering a sermon on the sacrifice of Jesus - Mumbai Archive Project Team (Jio Institute, 2024)
Father Michael Goveas, Vice-Rector of the Basilica of Our Lady of Mount, delivers a sermon elucidating the significance of Jesus’ sacrifice and its relevance to the lives of the faithful.